Quality Assessment of Freeform Surface Manufactured by CNC Milling Using Point Cloud Data Obtained from Different Scanning Devices - Vinh-Hung Tran (Springer, 2022)
Mechanical elements with freeform surfaces are very common in aerospace, automotive, mold and die industries. With increasing demand for higher quality of freeform surfaces in many different applications, quality monitoring and evaluation of freeform surfaces have become of great concern in modern manufacturing. In this study, quality evaluation of a freeform surface manufactured by CNC milling was carried out. First, the point cloud data of a given freeform surface sample manufactured by stamping were acquired by using different scanning systems, namely HandySCAN 3D 700 and ATOS Compact Scan 5M. Based on the point cloud data, the toolpaths, including roughing, semi-finishing, and finishing, were generated using computer-aided manufacturing (CAM) software. Milling experiments were then conducted on a 3-axis CNC milling machine to fabricate two freeform surface samples using the generated toolpaths. Finally, surface roughness and form deviation of the specimens were measured. The study results revealed the influence of point cloud data on the quality of the milled sample surfaces.